AN ANALYSIS OF THE IMPACT OF FOUR GRDP SECTORS ON THE HUMAN DEVELOPMENT INDEX IN THE DISTRICT OF SOLO REGION - Rifqi Iqbal Alwi; Siti Aisyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
One factor that serves as a barometer for a society's welfare in a place is human development. Human development must focus on the fields of education, agriculture, industry, and trade during this process if it is to achieve its objectives of raising living standards or improving the quality of human life. The Human Progress Index can be used to evaluate the primary indices of human development (IPM). Thus, this study aims to measure and determine the influence of the Gross Regional Domestic Product (GRDP) in the trade sector, the Gross Regional Domestic Product (GRDP) in the industrial sector, and the Gross Regional Domestic Product (GRDP) in the education services sector. and the Gross Regional Domestic Product (GRDP) of the agricultural sector on the Human Development Index (IPM) of the Districs in Solo Region. The method used in this study was panel data regression using secondary data cross section and time series from 7 districs in Solo Region which include Surakarta, Sukoharjo, Wonogiri, Sragen, Karanganyar, Boyolali, and Klaten in the last five years from 2016 to 2020. The variables in this study were the Gross Regional Domestic Product (GRDP) variables in the industrial, education, agricultural, trade and Human Development Index (IPM) sectors obtained from the Central Bureau of Statistics of Solo Region. This study shows that the industrial and education sector variables have a positive effect on the district human development index in Solo Region, while the agricultural and trade sector variables have a negative effect on the district human development index in Solo Region. . Keywords: Gross Regional Domestic Product, Human Development Index, Education, Agriculture, Industry.